2021
DOI: 10.1177/03635465211062609
|View full text |Cite
|
Sign up to set email alerts
|

ACL Reconstruction Combined With the Arnold-Coker Modification of the MacIntosh Lateral Extra-articular Tenodesis: Long-term Clinical and Radiological Outcomes

Abstract: Background: Interest in the role of lateral extra-articular tenodesis (LET) in preventing rotatory instability and the pivot-shift phenomenon after anterior cruciate ligament reconstruction (ACLR) has been recently renewed. Nevertheless, there is still concern about overconstraint of the lateral compartment of the knee and the risk of subsequent osteoarthritis (OA). Purpose: The purpose of this retrospective study was to compare long-term subjective and objective outcomes and the rate of OA development between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…On the other hand, large pretension values lead to an overconstrained knee behavior regarding ETR [ 28 ]. However, while knee overconstraint has been reported in similar clinical studies, its effect on knee range of motion and early OA onset is still a debatable topic [ 48 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, large pretension values lead to an overconstrained knee behavior regarding ETR [ 28 ]. However, while knee overconstraint has been reported in similar clinical studies, its effect on knee range of motion and early OA onset is still a debatable topic [ 48 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies with long-term follow-ups ranging from 20 to 25 years demonstrate high patient-satisfaction rates [49,50]. Moreover, combining a lateral extra-articular tenodesis with anterior cruciate ligament reconstruction has shown long-term protective effects in reducing the risk of arthritis compared to isolated ACL reconstruction [51].…”
Section: Discussionmentioning
confidence: 99%
“…15,16 Multiple studies have shown that performing a lateral extra-articular tenodesis (LET) in combination with ACLR is effective in reducing persistent anterolateral rotatory laxity, as measured by the pivot shift, and graft failure. 3,19,22,32,33,51 The STABILITY 1 multicenter randomized controlled trial demonstrated that patients who underwent primary ACLR…”
mentioning
confidence: 99%
“…15,16 Multiple studies have shown that performing a lateral extra-articular tenodesis (LET) in combination with ACLR is effective in reducing persistent anterolateral rotatory laxity, as measured by the pivot shift, and graft failure. 3,19,22,32,33,51 The STABILITY 1 multicenter randomized controlled trial demonstrated that patients who underwent primary ACLR with hamstring tendon autograft had an 11% graft failure rate, whereas the addition of an iliotibial band (ITB)–based LET resulted in a significantly reduced graft rupture rate (4%) in patients who were deemed to be at high risk of reinjury after ACLR. 19 However, there remains a concern as to whether an ITB-based LET may cause overconstraint of the tibiofemoral joint, leading to cartilage damage.…”
mentioning
confidence: 99%